Review of the bee genus Lasioglossum Curtis, 1833 (Hymenoptera: Halictidae) fauna of the Ciscaucasia region - Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2025)
Available information about bees of the genus Lasioglossum in the Ciscaucasia region is summarised. Ninety-one species are currently known from this territory. Lasioglossum ekaterinae sp. nov. is described as new to science from Russia (Dagestan and Kalmyk Republics) and Azerbaijan. Seven species are newly recorded from the Caucasus region and additional twenty species are newly recorded from Ciscaucasia. Six species are excluded from the list of the Ciscaucasia fauna. Including the new data, Russia’s fauna now includes 163 Lasioglossum species.